Loan process of micro credit loan: a case study on Agrobank branch of Melaka / Siti Salbiyah Md Said - Md Said, Siti Salbiyah (2010)
The aim of this paper is to investigate about how credit department handling micro credit loan process how they make delegation of work in a loan process. This research has been conducted on Agrobank branch of Melaka to investigate the issues. The objective of this research is to show on how credit department make a monitoring and follow up at every stage of loan process. Early monitoring and follow up will reduce the probability for the loan to become default loan. Thus, it needs a good delegation of works to ensure each steps in loan process gets the co-operation from a credit staff. The result of the study shows that Agrobank did not follow some steps in a loan process.